The International Cancer Expert Corps: A Unique Approach for Sustainable Cancer Care in Low and Lower-Middle Income Countries - Coleman, C. Norman; Formenti, Silvia C.; Williams, Tim R.; Petereit, Daniel G.; Soo, Khee C.; Wong, John; Chao, Nelson; Shulman, Lawrence N.; Grover, Surbhi; Magrath, Ian; Hahn, Stephen; Liu, Fei-Fei; et al. (Frontiers in Oncology, 2014)
The growing burden of non-communicable diseases including cancer in low- and lower-middle income countries (LMICs) and in geographic-access limited settings within resource-rich countries requires effective and sustainable solutions. The International Cancer Expert Corps is pioneering a novel global mentorship-partnership model to address workforce capability and capacity within cancer disparities regions built on the requirement for local investment in personnel and infrastructure. Radiation oncology will be a key component given its efficacy for cure even for the advanced stages of disease often encountered and for palliation. The goal for an ICEC Center within these health disparities settings is to develop and retain a high quality sustainable workforce who can provide the best possible cancer care, conduct research and become a regional center of excellence. The ICEC Center can also serve as a focal point for economic, social and healthcare system improvement. ICEC is establishing teams of Experts with expertise to mentor in the broad range of subjects required to establish and sustain cancer care programs. The Hubs are cancer centers or other groups and professional societies in resource-rich settings that will comprise the global infrastructure coordinated by ICEC Central. A transformational tenet of ICEC is that altruistic, human-service activity should be an integral part of a healthcare career. To achieve a critical mass of mentors ICEC is working with three groups: academia, private practice and senior mentors/retirees. While in-kind support will be important, ICEC seeks support for the career time dedicated to this activity through grants, government support, industry and philanthropy. Providing care for people with cancer in LMICs has been a recalcitrant problem. The alarming increase in the global burden of cancer in LMICs underscores the urgency and makes this an opportune time for novel and sustainable solutions to transform cancer care globally.